P-019 Comparative effectiveness of stent-assisted coiling and woven endobridge (WEB) embolization for the treatment of unruptured wide-neck bifurcation intracranial aneurysms. (23rd July 2022) - Kashkoush, A; Desai, A; Davison, M; Achey, R; Mahapatra, A; Patterson, T; Moore, N; Bain, M
Abstract : Introduction: Woven EndoBridge (WEB) intrasaccular flow disruptors and stent-assisted coiling (SAC) are viable endovascular treatment options for wide-neck bifurcation intracranial aneurysms (WNBAs). Data directly comparing the two treatment options are limited. We aim to compare radiographic occlusion rates and the complication profile between both. Methods: Retrospective review of a prospectively maintained cerebrovascular procedural database was performed at a single academic medical center between 2017 and 2021. Patients were included if they underwent WEB-embolization or SAC of an unruptured WNBA. SAC patients were propensity-matched to WEB-embolized patients based on aneurysm morphology. Complete and adequate (complete occlusion or residual neck remnant) occlusion rates at last angiographic follow-up as well as periprocedural complications were compared between the two groups. Results: Twenty-seven WEB and 54 SAC patients were included. Aneurysm width, neck size, and dome-to-neck ratio (DNR) were comparable between groups. Follow-up duration was significantly higher in the SAC group (median 504 [interquartile range, 196–791] vs. 203 [113–494] days, p=0.001, Mann Whitney U-test). Complete (WEB 67%, stent-coil 65%) and adequate (WEB 93%, stent-coil 91%) occlusion rates were similar between groups at last available angiographic follow-up (p=1.000, Chi-square test). Complete occlusion rates were comparable on Cox regression analysis after correction for follow-up duration (hazard ratio 1.3 [95% CI: 0.6–2.9]). Periprocedural complications trended higher in the SAC group (WEB 0% vs. stent-coil 13%, p=0.089, Fisher Exact test). Conclusion: Mid-term complete and adequate occlusion rates were similar between patients treated with WEB and SAC. Given the comparable outcomes, there may be equipoise in treatment options for WNBAs. Disclosures: A. Kashkoush: None. A. Desai: None. M. Davison: None. R. Achey: None. A. Mahapatra: None. T. Patterson: None. N. Moore: None. M. Bain: 2; C; Stryker Corporation.